Voluntary Refusal to Commit a Crime: Significance, General and Special Signs - Bezugly, Sergej N. (2022)
The article describes and examines the significance of the rule of the voluntary refusal to commit a crime, as well as explores its general and special signs. It is noted that the voluntary refusal to commit a crime is the rule contained in any modern, progressive law. In this vein, there are different theoretical approaches to the determination of its value and signs. The signs are debatable in nature, and their establishment by the law enforcer may cause difficulties. The difference between voluntary refusal to commit a crime, which is implemented in three functions, is determined, definitions of general signs of voluntary refusal are proposed, their content is clarified. Special signs of voluntary refusal are disclosed